García Lorca at the edge of surrealism : the aesthetics of anguish - Richter, David F., 1977- (Bucknell University Press ; Copublished by The Rowman and Littlefield Publishing Group, Incorporated, 2014)
"García Lorca at the Edge of Surrealism: The Aesthetics of Anguish examines the variations of surrealism and surrealist theories in the Spanish context, studied through the poetry, drama, and drawings of Federico García Lorca (1898-1936). In contrast to the idealist and subconscious tenets espoused by surrealist leader André Breton, which focus on the marvelous, automatic creative processes, and sublimated depictions of reality, Lorca's surrealist impulse follows a trajectory more in line with the theories of French intellectuals such as Georges Bataille (1897-1962), who was expulsed from Breton's authoritative group. Bataille critiques the lofty goals and ideals of Bretonian surrealism in the pages of the cultural and anthropological review Documents (1929-1930) in terms of a dissident surrealist ethno-poetics. This brand of the surreal underscores the prevalence of the bleak or darker aspects of reality: crisis, primitive sacrifice, the death drive, and the violent representation of existence portrayed through formless base matter such as blood, excrement, and fragmented bodies. Drawing extensively on the theoretical, cultural, and poetic texts of the period, García Lorca at the Edge of Surrealism offers the first book-length study to consider Bataille's thinking within the Spanish context, examined through the work of Lorca, a singular exponent of what is here referred to as a dissident Spanish surrealism. By reading Lorca's "surrealist" texts (including Poeta en Nueva York, Viaje a la luna, and El público) through the Bataillean lens, this volume both amplifies our understanding of the poetry and drama of one of the most important Spanish writers of the twentieth century and also expands our perspective of what surrealism in Spain means" --